Pendidikan Akhlak Ibnu Maskawaih - Herningrum, Indah; Alfian, Muhammad (Pusat Penelitian dan Pegabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2019)
Ibn Makawaih is a philosopher who focuses on morals. Ibn Miskawaih states that morality is a state of the soul of a person who encourages to do something without going through consideration of thoughts first. The purpose of moral education formulated by Ibn Miskawaih is the realization of an inner attitude that is able to encourage spontaneously to give birth to all good-value actions so that they can achieve perfection and obtain true and perfect happiness. There are three important things that can be understood as moral education material, namely: things that are obligatory for the needs of the human body, things that are obligatory for the soul and things that are obligatory for their relationship with fellow human beings. Ibn Miskawaih in his character concept emphasizes psychological and religious aspects to improve the quality of one's character.